MEDSEA: a small open economy DSGE model for Malta - Noel Rapa (Central Bank of Malta, 2016)
This paper describes MEDSEA, a compact small open economy DSGE model of the Maltese economy. The model is similar in nature to other small open economy models, thus containing a number of nominal and real frictions allowing the model to replicate the sluggish reaction of economic variables documented in empirical research. Moreover, MEDSEA contains key modifications designed to account for Malta's specific characteristics. The model distinguishes between a tradable and non-tradable sector reflecting the different nature of exports when compared to other production meant for domestic use. Furthermore, the model features distribution costs in the export sector allowing for a wedge to exist between wholesale and retail export prices.
Keywords: E12; E30; E50; 330